Perfil bibliométrico de la Revista Peruana de Investigación Educativa de la SIEP en sus primeros años (2009-2020) - Montes Iturrizaga, Iván (2022)
This article presents the results of an analytical and bibliometric study on the Peruvian Journal of Educational Research of the Peruvian Society for Peruvian Educational Research (SIEP). We worked on the basis of 75 articles published in this journal and the data was processed through the Google Scholar report, to obtain a profile according to the following bibliometric indicators: authors, gender of the authors, belonging to the SIEP, nationality, institution from which they come, thematic axes, methodological approach and the impact according to the citations registered in the Google Scholar. The results of this study offer insights about the composition of the journal, the methodologies favored by the authors who see this medium as a legitimate way of dissemination, and national and international citations, among others. Likewise, it is concluded that the journal is not an endogamous publication, more women publish than men, it has a low rate of internationalization and the most cited authors are: Ricardo Cuenca, Javier Murillo and Mercedes Loza, among others.